O relatório de gestão como instrumento de avaliação do acesso ao sistema de saúde - Marchionatti, Carmem Regina Estivalete (Universidade do Vale do Rio do Sinos, 2006)
This article aims to discuss the potentialities of the City’s Health Management Report (CHMR) as an instrument to evaluate the access to health services provided by SUS. Using scientific literature, a research was carried out to know the most commonly used indicators to measure the access to health services. Indicators were selected from both national and international literature. Afterwards, the chosen indicators were compared to those used by CHMR, identifying coincidences, and making a selection of the access indicators used by CHMR. Finally, we discussed the potentialities and limitations of such indicators to evaluate access to SUS. We came to the conclusion that the CHMR consists of indirect access measures through which it is possible to suggest hypotheses related to access problems which might influence the performance of coverage and service use indicators. The access evaluation in different social groups is limited, due to the lack of social variables in the Health Information Systems. Some indicato
Keywords: gestão; instrumento de avaliação; Sistema Único de Saúde; Ciências da Saúde